A Distinct Clinicopathological Feature and Prognosis of Young Gastric Cancer Patients Aged ≤ 45 Years Old - Huang, Qian; Zheng, Xiufeng; Jiao, Yang; Lei, Yanna; Li, Xiaoying; Bi, Feng; Guo, Fukun; Wang, Gang; Liu, Ming (Frontiers in Oncology, 2021)
Purpose The aim of this retrospective study was to probe into clinicopathological features and prognosis of early-onset gastric cancer (EOGC) patients aged ≤ 45 years old. Methods This study selected 154 young gastric cancer patients aged ≤ 45 years old and 158 elderly gastric cancer patients aged > 50 years old admitted to West China Hospital of Sichuan University in 2009-2019 as the research object. These patients were further divided into two groups according to whether tumor can be resected radically. The following parameters were analyzed: age, gender, helicobacter pylori (HP) infection status, Her-2 status, pathological type and stage, chemotherapy, tumor differentiation degree, overall survival (OS). Results More than 3,000 patients with gastric carcinoma were screened, and 154 young gastric cancer patients aged ≤ 45 years old were identified as EOGC. Among them, the number of female patients in EOGC group was significantly higher than that of males, accounting for 63.6%. In addition, EOGC were associated with diffuse Laur´en type and poorly differentiated tumors. Interestingly, the Kaplan–Meier method showed that the OS of unresectable EOGC group was significantly lower than that of unresectable LOGC group (P = 0.0005) and chemotherapy containing paclitaxel tended to be more effective in the young people (P = 0.0511). Nevertheless, there was no significant difference in OS between young and elderly patients with gastric cancer in the radical resection group (P = 0.3881). Conclusion EOGC patients have a worse prognosis than late-onset gastric cancer (LOGC) patients with advanced unresectable gastric cancer. Palliative surgery or chemotherapy containing paclitaxel may improve the OS of unresectable young individuals with gastric cancer. Additional randomized controlled trials are required for guiding clinical practice.